Digital Divide and Digital Literacy During the Covid-19 Pandemic - Valentia, Tetta Riyani (Institute of Research and Community Outreach - Petra Christian University, 2023)
The Covid-19 pandemic has had a huge impact on the lives of people, where technology plays an important role in people’s daily lives, including the education sector. This is also reinforced by the rampant digital revolution (4.0) and triggers countries to prepare human resources that can compete in the global scope. This situation requires ICT skills that need to be possessed by every level of society. However, the development of ICT in Indonesia is still uneven and has resulted in a digital divide. Technology has been included in primary needs, and it is reflected in the education sector. This study aims to provide a comprehensive picture of the gap and digital literacy in online learning during pandemic. This study used a qualitative descriptive method where data were collected through literature study. The result of this study indicates that in general Indonesia has a diverse digital divide, ranging from ownership of access, the usage of ICT, to the quality of using ICT. This is inseparable from the differences in the geographical and socio-demographic conditions of the Indonesian. All efforts that have been planned and implemented are increasingly understood to be carried out properly, acceleration of digital literacy is the main key in dealing with the digital divide, especially in terms of education.